2018
DOI: 10.1109/tnnls.2018.2816518
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Learning in a Cognitive Neuromorphic Robot: An Integrative Approach

Abstract: We present here a learning system using the iCub humanoid robot and the SpiNNaker neuromorphic chip to solve the real-world task of object-specific attention. Integrating spiking neural networks with robots introduces considerable complexity for questionable benefit if the objective is simply task performance. But, we suggest, in a cognitive robotics context, where the goal is understanding how to compute, such an approach may yield useful insights to neural architecture as well as learned behavior, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…There are many examples of converting data directly from sensors [19][20][21], intelligent systems with controlling manipulators [11] [22], and robots [23][24] [25]. Moreover, performing detection and recognition tasks [26][27] [28], and processing numerical data with Neural Engineering Framework (NEF) [29][30] [31] can also be done with SNNs.…”
Section: Spiking Neural Network (Snn)mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many examples of converting data directly from sensors [19][20][21], intelligent systems with controlling manipulators [11] [22], and robots [23][24] [25]. Moreover, performing detection and recognition tasks [26][27] [28], and processing numerical data with Neural Engineering Framework (NEF) [29][30] [31] can also be done with SNNs.…”
Section: Spiking Neural Network (Snn)mentioning
confidence: 99%
“…While much research has been conducted on vision-based identification, the combination of vision and non-vision sensors promise improvements in the speed of the recognition process. Rast et al [28], demonstrated the learning system using an iCub robot and a SpiNNaker system to solve object identification tasks. The SpiNNaker neuromorphic system [122] is a neural network simulation platform, designed for real-time simulations.…”
Section: A Signal Acquisition and Processing Applicationsmentioning
confidence: 99%
“…A universal event‐driven neuromorphic robotic computing platform was established [150]. Chen et al [151] and Rast et al [152] recently introduced SpiNNaker on a snake‐shaped robot and an iCub humanoid platform, respectively, to realize perception processing.…”
Section: Tactile Neuromorphic Computingmentioning
confidence: 99%
“…A more detailed description of the framework for simulating neural networks is found in Rhodes et al (2018), but we examine here the application from the perspective of the tools. SpiNNTools has been part of the sPyNNaker software since conception and this release is successfully deployed as part of the EU Flagship Human Brain Project Collaboratory 6 , and has been used successfully in a number of simulations in previous works (e.g., Senk et al, 2017; Albada et al, 2018; Rast et al, 2018; Sen-bhattacharya et al, 2018).…”
Section: Use Casesmentioning
confidence: 99%
“…The live output example described in the Conway's use case also works similarly well in the neural networks use case. Another extension more relevant here is the connection of an external device to the machine which will then be controlled by the network (e.g., a robotic device), as was the subject of Rast et al (2018). In this case an extension of the virtual application vertex is made to represent the device and added to the application graph.…”
Section: Use Casesmentioning
confidence: 99%